Expression levels of FSHR, IGF1R, CYP11al and HSD3β in cumulus cells can predict in vitro developmental competence of bovine oocytes. Issue 5 (2nd October 2020) - Khurchabilig, Atchalalt; Sato, Akane; Ashibe, Shiori; Hara, Asuka; Fukumori, Rika; Nagao, Yoshikazu
Summary: The efficiency of in vitro embryo production technologies would be improved by the development of suitable non-invasive biomarkers that allow the selection of good quality cumulus–oocyte complexes (COCs). The present study used whole, single oocyte culture to investigate whether the expression levels of follicle-stimulating hormone receptor (FSHR), insulin-like factor 1 receptor (IGF1R) and three steroidogenesis-related enzymes (CYP11al, CYP19al and HSD3β) in cumulus cells reflected the developmental competence of COCs. Cumulus cells were collected from single COCs before maturation culture and relative mRNA levels were assessed using real-time PCR. The analysis indicated that mRNAs for FSHR, IGF1R, CYP11al and HSD3β were present at higher levels in cumulus cells from COCs that failed to form blastocysts compared with cumulus cells from COCs that formed blastocysts. Moreover, FSHR and IGF1R mRNA levels were positively correlated with those of genes for steroidogenesis-related enzymes. In conclusion, poor developmental competence of COCs was related to higher expression of FSHR, IGF1R, CYP11al and HSD3β in cumulus cells, which may indicate the advanced differentiation of cumulus cells into granulosa cells.